Numerical Analysis of Seepage in Earth-Fill Dams - Nassrin Jassim Hussien Al-Mansori; Thair AL-Fatlawi Jabbar Mizhir Al-Fatlawi; Nariman Yahya Othman; Laith Shaker Ashoor Al-Zubaidi (Salehan Institute of Higher Education, 2020)
In an earth-fill dam, the effect of seepage has been studied by applying a finite element method using the SEEP2D program. This is in order to determine the quantity of seepage through the dam. The total head measurements, core permeability, and anisotropy ratio (kx/ky) (Case study: Khassa Chai Dam, Iraq) are taken as the main parameters. The effect of the different water heads of the reservoir were tested on the seepage. The results showed that any increase in the water heads caused an increase in seepage quantity. Also, it was found that the seepage rate decreases by about 8.7%, 13.2%, and 15.3% at levels of water 454, 471, and 485 m.a.s.l, respectively by changing the core permeability from 10-6 m/s to 10-7 m/s. It has been concluded that the clay core plays a significant role in decreasing the seepage quantity and existing gradient. The results of testing the effect of anisotropy ratio on seepage showed that an increase in (kx/ky) ratio leads to an increase in seepage quantity. Output variables and input variables have been linked by the ANN model that governs seepage quantity through zoned earth dams and existed gradients. The results showed that both models present a good estimation for the determination of coefficient R2 (0.9003, 0.933).